#### Answer

{$\frac{-1}{2}$}

#### Work Step by Step

-6x =3
Step 1: Divide both the sides by -6
$\frac{-6x}{-6}$ = $\frac{3}{-6}$
Step 2: Simplify
x= $\frac{-1}{2}$
Now we check the proposed solution, $\frac{-1}{2}$, by replacing x with $\frac{-1}{2}$ in the original equation.
Step 1: the original equation -6x =3
Step2: Substitute $\frac{-1}{2}$ for x
-6.($\frac{-1}{2}$) = 3
Step 3: Solve -6. ($\frac{-1}{2}$) = 3
3=3
Since the check results in true statement, we conclude that the solution set of the given equation is {$\frac{-1}{2}$}